Islamic Tourism in Africa - R. I. Bekkin; A. S. Shnyrkova (Vestnik MGIMO-Universiteta)
The research aims to assess the prospects for the development of Islamic tourism in Africa. The authors analyze the notion and features of Islamic tourism and identify key differences between “Islamic tourism” and “Halal tourism.” The authors define “Islamic tourism” as a type of tourism that includes travels for any purpose under Islamic principles. The research mainly covers the development of Islamic tourism in African countries. For this purpose, it analyzes the tourist flows’ trends and the leading African touristic destinations, identifies the main Halal-friendly African destinations. The leading states here are Morocco, Egypt, and South Africa; Tunisia fosters its potential for Islamic medical tourism; Senegal and Mali are attractive due to Islamic heritage sites. The main problems for the development of Islamic tourism in Africa have also been identified: underdeveloped tourist and Halal infrastructure, lack of security, and poor promotion of tourist services among potential tourists are among the most significant ones. The study has found that popular Halal destinations are countries with a predominantly Muslim population and states where Muslims are a minority. Despite the restrictions followed by COVID-19 and a significant decrease in the tourism sector, a return to the previous volumes of tourist flows and income is expected in 2023. The World Tourism Organization actively supports the recovery and development of tourism in African countries. The improvement of Halal infrastructure and new facilities for this type of tourism will contribute to an overall increase in income from tourism activities and the popularization of Islamic tourism.